2017
DOI: 10.1002/ejoc.201601271
|View full text |Cite
|
Sign up to set email alerts
|

Modular Urea‐Based Catalytic Platforms Bearing Flexible Pyridylmethylamine and Rigid Pyridyl‐Imidazolidine Fragments

Abstract: The selective and concise synthesis of new urea‐based catalytic platforms is described. Each platform incorporates a urea or thiourea motif with a pyridylmethylamine or pyridyl‐imidazolidine fragment. These modular catalytic platforms efficiently promote Michael addition reactions. Moreover, the corresponding Cu complexes successfully catalyse Henry‐type reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Following our interest in non-covalent interactions, 19,20 we focused on the tetrazine ring, which exhibits both excellent photophysical 21–24 and anion–π binding properties. 25,26 We recently showed that photophysical properties are particularly useful to characterize anion complexes in solution in a new anion receptor (1) combining a tetrazine and an urea subunits linked by a short flexible arm.…”
Section: Introductionmentioning
confidence: 99%
“…Following our interest in non-covalent interactions, 19,20 we focused on the tetrazine ring, which exhibits both excellent photophysical 21–24 and anion–π binding properties. 25,26 We recently showed that photophysical properties are particularly useful to characterize anion complexes in solution in a new anion receptor (1) combining a tetrazine and an urea subunits linked by a short flexible arm.…”
Section: Introductionmentioning
confidence: 99%
“…Alongside highly pre-organized rigid receptors widely spread in supramolecular chemistry, [15] we focused our attention on single molecules comprising a hydrogen bonding donor linked to a deficient heterocycle able to generate anion-interactions. Based on our recent publications [16][17][18][19][20][21] and publications from Melguizo and Bianchi, [22,23] we envisioned that the combination of urea and tetrazine moieties would be beneficial to anion binding and allow cross-characterisation of binding properties. On one hand, the urea motif would enable gaining information from 1 H NMR techniques and on the second we take benefits from the dual role of the tetrazine fragment acting as anion-acceptor and as fluorescent probe (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…11 Such compounds revealed especially valuable as catalytic systems in various synthetic organo-and metallo-promoted transformations including oxidative C-C bond formation, cycloaddition reactions, Friedel-Crafts alkylation, Henry reaction, Suzuki coupling, C-H arylation. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Figure 1. Pma modulation sites, transition metal and proton complexes and Zn II and Co II complexes.…”
mentioning
confidence: 99%